STUDY OF ELECTRICITY QUALITY INDICATORS IN INDUSTRIAL ENTERPRISES - Mirzayev Uchqun; Istamov Og‘abek (Ta’lim innovatsiyasi va integratsiyasi, 2024)
ABSTRACT Power supply of industrial enterprises, factors influencing the quality of electricity in enterprises and their economic losses, management of power supply systems in industrial enterprises, evaluation of electrical parameters in industrial enterprises, synchronized vector measurement system errors, vector measurement system accuracy assessment, industrial enterprise power supply system to study technical solutions to achieve energy efficiency by improving quality indicators.